Sistem Kendali Navigasi Robot Manual - Sapta Nugraha (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
The purpose of this study is to control the robot's navigation manually and determine the coordinate position and movement patterns of the manual robot. This study uses GPS to determine the position of coordinates and patterns of manual robot movements. Manual robot navigation control systems use wireless joysticks and use of omni wheels on manual robot mechanics to maneuver movements in all directions.  The control device uses the Serial Peripheral Interface (SPI) communication by utilizing the nRF24L01 communication device on the 2.4 GHz RF band. The results showed that the position and pattern of manual robot navigation movements can be known based on the coordinate points on the route taken. In addition, wireless joysticks can control manual robots to maneuver the movements of manual robots in all directions.